2010
DOI: 10.3758/s13423-010-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Scale and construal: How larger measurement units shrink length estimates and expand mental horizons

Abstract: Scale can vary by requiring a different number of units to measure the same target. But what are the consequences of using fewer, larger units? We draw on past psychophysical research that shows how using fewer units reduces clutter in measurement, translating to shorter length estimates. Additionally, we propose that larger scale is associated with targets further from a person's immediate experience (i.e., psychologically distant) and higher order mental representation. Evidence from Study 1 indicates that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Though the current investigation sampled only two phenomena, we believe that a similar effect of abstract construal should generalize across a wide range of contextual bodily states, including smell (Liljenquist, Zhong, & Galinsky, 2010), sight (Zhong, Bohns, & Gino, 2010), and others. In addition, as the different dimensions of psychological distance produce similar effects on judgment (Henderson & Wakslak, 2010), our results should replicate beyond temporal distance as well as to other manipulations of construal (e.g., Kross et al, 2005;Maglio & Trope, 2011). Importantly, incidental proprioceptive feedback can at times prove advantageous, highlighting the value of concrete thinking.…”
Section: Discussionmentioning
confidence: 96%
“…Though the current investigation sampled only two phenomena, we believe that a similar effect of abstract construal should generalize across a wide range of contextual bodily states, including smell (Liljenquist, Zhong, & Galinsky, 2010), sight (Zhong, Bohns, & Gino, 2010), and others. In addition, as the different dimensions of psychological distance produce similar effects on judgment (Henderson & Wakslak, 2010), our results should replicate beyond temporal distance as well as to other manipulations of construal (e.g., Kross et al, 2005;Maglio & Trope, 2011). Importantly, incidental proprioceptive feedback can at times prove advantageous, highlighting the value of concrete thinking.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, in our research we have assumed that construal level affects the cognitive representation of perceived distance toward the target rather than of the reference scale, in which case an abstract (concrete) mindset would have led to lower (higher) perceived distance (Maglio & Trope, 2011). Although our results are in line with an assimilation effect of construal level and distance, future research could explore when people are inclined to focus on the reference scale rather than the target and hence when a contrast effect of construal level and distance can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Liberman and Förster (2009b) found that priming people with a sense of distance led to faster recognition of global aspects and slower recognition local aspects of stimuli. Furthermore, Maglio and Trope (2011) found that the physical length between two points on a map were estimated using larger units of measurement when the path where described as spatially distant rather than near. We suggest that this expanding of one's mental horizon is likely to affect predictions of task duration, as well.…”
Section: Psychological Distance and Construal Levelsmentioning
confidence: 98%